1983
DOI: 10.1136/hrt.50.3.273
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology of chronic constrictive pericarditis.

Abstract: In a consecutive series of 32 cases of chronic constrictive pericarditis treated by pericardiectomy during the past 25 years, four were attributable to rheumatoid disease, two to trauma, one to sarcoidosis, and four, at a maximum, to tuberculosis. In the remaining 21 cases of undetermined aetiology there was no evidence of tuberculosis. It appears, therefore, that tuberculosis was not a common cause of chronic constrictive pericarditis during the period under review, which included the 1950s and early 1960s wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Nor did any develop constrictive pericarditis. 15 That may be explained in part because we did not encounter any instance of tuberculous effusion, an aetiology which is well known to result in constrictive pericarditis 16 (see addendum). Despite previous reports of development of constriction subsequent to bacterial pericarditis, 7,8,17 we have not yet encountered this complication, which may occur even without evidence of earlier pericardial disease.…”
Section: Discussionmentioning
confidence: 97%
“…Nor did any develop constrictive pericarditis. 15 That may be explained in part because we did not encounter any instance of tuberculous effusion, an aetiology which is well known to result in constrictive pericarditis 16 (see addendum). Despite previous reports of development of constriction subsequent to bacterial pericarditis, 7,8,17 we have not yet encountered this complication, which may occur even without evidence of earlier pericardial disease.…”
Section: Discussionmentioning
confidence: 97%
“…14,15 We screened our patient for the rarer cause of tuberculosis. 16 We found only 2 reports of constrictive pericarditis associated with CS. The first patient was a young man whose presentation was similar to that of our patient.…”
Section: Fig 5 Cardiovascular Magnetic Resonance Image Shows Late Enhancement In the Anteroseptal And Basal Inferolateral Segments Of Thementioning
confidence: 89%
“…In group A 50% were tuberculous while in B, no evidence of TB. Some authors reported up to 60% tuberculous cases in the classic type (16,17,18) .…”
Section: Discussionmentioning
confidence: 99%